Central nervous system involvement in a case of segmental nevus depigmentosus - Ishita Majumdar; Devdeep Mukherjee; Sandipan Dhar; Ritabrata Kundu (Wolters Kluwer Medknow Publications, 2016)
Central nervous system involvement in segmental nevus depigmentosus (SND) is rare. A 7-month-old boy having convulsion and segmental hypopigmented patch in the right inguinal region. Magnetic resonance imaging of brain showed bilateral periventricular white matter hypoplasia with prominent subarachnoid spaces and mild dilation of ventricles with mild left cerebral hemispheric atrophy. Association of SND with seizure and white matter lesion has been rarely reported.